Preventing workplace violence : a training guide for managers and supervisors : proven practices - Jackson, Rosalind W. (Security Executive Council risk management portfolio., 2015)
Preventing Workplace Violence: A Training Guide for Managers and Supervisors is a video presentation. Length: 25 minutes. In Preventing Workplace Violence: A Training Guide for Managers and Supervisors, presenter Rosalind W. Jackson provides the fundamentals of workplace violence prevention, including initial program development. This presentation explains the components needed to develop a good baseline program, and focuses on recognizing patterns of unacceptable behavior. It addresses policy development and expert consultation considerations, along with the use of education and team coordi.